2022
DOI: 10.1007/s40145-022-0609-z
|View full text |Cite
|
Sign up to set email alerts
|

(Ho0.25Lu0.25Yb0.25Eu0.25)2SiO5 high-entropy ceramic with low thermal conductivity, tunable thermal expansion coefficient, and excellent resistance to CMAS corrosion

Abstract: Low thermal conductivity, compatible thermal expansion coefficient, and good calcium—magnesium—aluminosilicate (CMAS) corrosion resistance are critical requirements of environmental barrier coatings for silicon-based ceramics. Rare earth silicates have been recognized as one of the most promising environmental barrier coating candidates for good water vapor corrosion resistance. However, the relatively high thermal conductivity and high thermal expansion coefficient limit the practical application. Inspired by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 54 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…It is further concluded that RETaO 4 is a promising high-temperature TBCs with low thermal conductivity and ferroelastic toughening effect similar to YSZ. Some experimental works have been done to further reduce the lattice thermal conductivity (κ) by oxide doping, [25][26][27] double rare-earth doping 24,28 , or synthesis of high entropy ceramics, [29][30][31][32][33][34][35] of which Y 1/6 Yb 5/6 TaO 4 has the smallest κ, only 66% of YTaO 4 and 47% of YSZ. However, previous experimental studies mainly focused on quantifying the thermophysical properties of m-RETaO 4 and their derivatives, whereas the underlying mechanism of low κ compared with YSZ cannot be well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is further concluded that RETaO 4 is a promising high-temperature TBCs with low thermal conductivity and ferroelastic toughening effect similar to YSZ. Some experimental works have been done to further reduce the lattice thermal conductivity (κ) by oxide doping, [25][26][27] double rare-earth doping 24,28 , or synthesis of high entropy ceramics, [29][30][31][32][33][34][35] of which Y 1/6 Yb 5/6 TaO 4 has the smallest κ, only 66% of YTaO 4 and 47% of YSZ. However, previous experimental studies mainly focused on quantifying the thermophysical properties of m-RETaO 4 and their derivatives, whereas the underlying mechanism of low κ compared with YSZ cannot be well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 summarizes the recently reported representative results with respect to the reaction layer thickness of RE silicates at a certain corrosion temperature and time. 14,19,[31][32][33][34][35][36][37][38][39] Ideally, the optimum result is to obtain a relatively low thickness for the reaction layer in a long-term high-temperature corrosion process. In reality, however, this approach is difficult to implement.…”
Section: Resultsmentioning
confidence: 99%
“…also reported the molten CMAS corrosion resistance of a high‐entropy (4RE 0.25 ) 2 Si 2 O 7 (RE = Er, Tm, Yb, and Lu) at high temperature. The results showed that the thickness of reaction layer was approximately 300 μm after corrosion at 1500°C for 50 h. Tian et al 18 . only measured the ability of high‐entropy RE monosilicate (( x RE 1/ x ) 2 SiO 5 (RE = Ho, Lu, Yb, and Eu)) to resist molten CMAS corrosion at low temperature, and its thickness of reaction layer was up to 125 μm after corrosion at 1300°C for 20 h. Therefore, we conclude that although the high‐entropy RE silicates showed a significant improvement in the corrosion resistance of molten CMAS compared to single‐component RE silicates, the thickness of the reaction layer was still very high during long‐term corrosion at high temperature, which will be catastrophic for EBCs with the thickness of only tens to hundreds of microns.…”
Section: Introductionmentioning
confidence: 94%
“…conductivity, high mechanical properties, and excellent thermal stability are critical for thermal insulation and protection of advanced equipment. Especially, the thermal insulating materials working under extreme conditions, such as long-term high-temperature (≥ 1000 ℃) exposure and rapid thermal shocking, are urgently required in the fields of aerospace, nuclear power engineering, and industry furnace [1,2]. In the past few decades, the ceramic fibers (such as SiO 2 , ZrO 2 , Al 2 O 3 , and mullite) are the most developed and widely investigated hightemperature thermal insulating materials due to their low density, low solid thermal conductivity, and excellent fire and high-temperature resistance [1][2][3][4][5][6].…”
Section: Introduction mentioning
confidence: 99%
“…Especially, the thermal insulating materials working under extreme conditions, such as long-term high-temperature (≥ 1000 ℃) exposure and rapid thermal shocking, are urgently required in the fields of aerospace, nuclear power engineering, and industry furnace [1,2]. In the past few decades, the ceramic fibers (such as SiO 2 , ZrO 2 , Al 2 O 3 , and mullite) are the most developed and widely investigated hightemperature thermal insulating materials due to their low density, low solid thermal conductivity, and excellent fire and high-temperature resistance [1][2][3][4][5][6]. They can be used as either flexible thermal insulators or reinforcements of aerogel thermal insulators, which are both urgently needed in high-temperature thermal insulation fields [7][8][9].…”
Section: Introduction mentioning
confidence: 99%